The international financial crisis : have the rules of finance changed? - Demirguc¸-Kunt, Asli , 1961-; Evanoff, Douglas Darrell , 1951-; Kaufman, George G. (World Scientific studies in international economics, 2011)
The global financial crisis has caused massive upheavals worldwide. This volume analyzes whether financial principles seem to have shifted, and what that may mean for international financial markets and regulation. It discusses these and related issues